Altered Joint Angle Strategy for Sprinting in Elite Sprinters with Chronic Ankle Instability - Hiroki Arakawa; Masamichi Okudaira; Satoru Tanigawa; Hirohiko Maemura; Takashi Fukuda (Asian Society of Kinesiology, 2023)
OBJECTIVES Individuals with chronic ankle instability (CAI) demonstrated altered not only ankle but also lower extremity joint angle during numerous dynamic movements compared to healthy controls. However, little is known about joint angles during sprinting, which is the most essential movement during explosive sports. We, therefore, investigated the lower extremity joint angle during sprinting between elite sprinters with CAI and healthy controls. METHODS Fourteen male college sprinters participated in this study, seven with CAI and seven healthy controls. Five-second steady speed running was performed on a treadmill at 7.5 m/s. Mean lower extremity joint angles were compared applying the statistical parametric mapping method. RESULTS The CAI patients demonstrated significantly higher ankle dorsiflexion and knee flexion angles during the stance phase. Additionally, large between-group effect sizes would demonstrate higher ankle dorsiflexion and knee and hip flexion angle from the late swing phase to the late stance phase. CONCLUSIONS The altered lower extremity joint angles from the late swing phase to the late stance phase in CAI patients suggest greater joint stability for large external loads with feed-forward motor control programs.